Synthesis and biological evaluation of curcumin-based fluorophores - Ferreira, Joana Raquel Mendes (2023)
Curcumin is a natural compound obtained from the rhizome of Curcuma longa. It has several properties of clinical interest such as antitumoral and antimicrobial properties and has been suggested as a photosensitizer in photodynamic therapy as an alternative therapy. Curcumin derivatives have also been used as fluorescent markers of protein aggregates in neurodegenerative diseases. In this work, a family of curcumin derivatives was synthesized, characterized and their photophysical properties were studied. The biological evaluation of these derivatives was studied in two cell models, the phytopathogenic fungus Fusarium oxysporum and the human cell line SH-SY5Y used in studies of neurodegenerative diseases, using cytotoxicity tests and fluorescence microscopy. The curcuminoids described were not toxic in the dark to the cell models under study and the location of some derivatives within the cells of the SH-SY5Y cell line is suggested.